INFORMATION AND KNOWLEDGE OF PUBLIC SECTOR DECISION MAKERS: EXPERIMENTAL RESEARCH IN THE CONTEXT OF A LOCAL GOVERNMENT HOSPITAL IN INDONESIA - Icuk Rangga Bawono; Abdul Halim; Beverley R. Lord (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This research aimed to test the previous result of experimental research on decision making by Dilla and Steinbart (2005), and to internalize the result in the context of a local government hospital in Indonesia. The subjects in this experiment were 80 members of the House of Representatives in the Cilacap, Brebes and Purbalingga regions in Indonesia. They were asked to evaluate the performance of a fictitious local government hospital and decide whether or notto increase its budget allocation for the coming year. Half of the subjects were given instruction in the performance measures applicable to hospitals; the other half proceeded straight to the experimental task. The first group were labelled “knowledgeable users”; the latter group were classified as “unknowledgeable”.The results of this experiment using real decision makers showed that the knowledgeable group tended to use the unique information given to them to measure performance and make budget allocation plans, whereas the unknowledgeable group used common measures. These results are consistent with Lipe and Salterio (2000), Dilla and Steinbart (2005) and Bawono etal. (2012), indicating that students may be reliable surrogates for real decision makers.Keywords: accountability, public sector, performance measurement, budget allocation plan, knowledgeable and unknowledgeable, decision makers